Teorias do direito administrativo global e standards: desafios à estatalidade do direito - Sousa, Otavio Augusto Venturini de (2019)
This research aims to understand and to test the analytical capacity of the theoretical framework called "Global Administrative Law" to categorize and to rule regulatory phenomena of non-state source, represented in this research by standards. The first chapter brings a study of the historicity of Euro-centric juridical statehood and the threshold of legal globalization. The second chapter, in its turn, intends to systematize different theoretical approaches to Global Administrative Law. The third chapter deals with the relation between the standards produced by nongovernmental organizations and the state legal order. The purpose of the chapter is to identify what is most challenging to the “dogmas” of the juridical statehood and to present the theoretical implications of the relationship between the standards and the state legal system, especially regarding the normative proposal of Global Administrative Law. The fourth chapter describes the problem situation of production and reception of ISO 37001 by the Brazilian legal system. The empirical study aims to serve as a verification field for the Global Administrative Law theory. Finally, the fifth chapter aims to draw conclusions about the relevance and usefulness of the theoretical framework of Global Administrative Law to categorize and to rule the production and the implications of normative phenomena of non-state source.